Role of the Material Electrodes on Resistive Behaviour of Carbon Nanotube-Based Gas Sensors for H2S Detection. (3rd June 2012) - Lucci, M.; Toschi, F.; Guglielmotti, V.; Orlanducci, S.; Terranova, M. L.
Abstract : Miniaturized gas-sensing devices that use single-walled carbon nanotubes as active material have been fabricated using two different electrode materials, namely, Au/Cr and NbN. The resistive sensors have been assembled aligning by dielectrophoresis the nanotube bundles between 40  μ m spaced Au/Cr or NbN multifinger electrodes. The sensing devices have been tested for detection of the H2 S gas, in the concentration range 10–100 ppm, using N2 as carrier gas. No resistance changes were detected using sensor fabricated with NbN electrodes, whereas the response of the sensor fabricated with Au/Cr electrodes was characterized by an increase of the resistance upon gas exposure. The main performances of this sensor are a detection limit for H2 S of 10 ppm and a recovery time of few minutes. The present study suggests that the mechanism involved in H2 S gas detection is not a direct charge transfer between molecules and nanotubes. The hypothesis is that detection occurs through passivation of the Au surfaces by H2 S molecules and modification of the contact resistance at the Au/nanotube interface.